2016
DOI: 10.2337/dc16-1898
|View full text |Cite
|
Sign up to set email alerts
|

Differential Patterns of Impaired Cardiorespiratory Fitness and Cardiac Autonomic Dysfunction in Recently Diagnosed Type 1 and Type 2 Diabetes

Abstract: CRF is reduced in recently diagnosed type 2 diabetes but preserved in type 1 diabetes, whereas cardiac autonomic function is reduced in both diabetes types but is strongly associated with CRF only in type 1 diabetes. These results support the therapeutic concept of promoting physical fitness in the early course of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 43 publications
2
22
0
Order By: Relevance
“…In the present study, after adjusting for CRF, it was observed that total sedentary time was only associated with HbA1c, whereas BST had favorable associations with HOMA-IR, Matsuda index, and fasting glucose. Thus, as previously shown (Ekblom-Bak et al, 2016; Rohling et al, 2016), CRF can neutralize most of the associations for total sedentary time with glycemic outcomes, and this may be explained by the association between total sedentary time and CRF itself (Krogh-Madsen et al, 2010). …”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…In the present study, after adjusting for CRF, it was observed that total sedentary time was only associated with HbA1c, whereas BST had favorable associations with HOMA-IR, Matsuda index, and fasting glucose. Thus, as previously shown (Ekblom-Bak et al, 2016; Rohling et al, 2016), CRF can neutralize most of the associations for total sedentary time with glycemic outcomes, and this may be explained by the association between total sedentary time and CRF itself (Krogh-Madsen et al, 2010). …”
Section: Discussionmentioning
confidence: 52%
“…Alongside with these results, replacing 30 min of sedentary time with LIPA provided higher benefits in metabolic profile in participants with lower CRF when compared with those with normal to high CRF levels (Ekblom-Bak et al, 2016), suggesting that the associations between sedentary pursuits and metabolic outcomes may be moderated by CRF. There is a lack of studies that analyzed the associations for sedentary time and respective patterns with glycemic indicators while adjusting for CRF (Ekblom-Bak et al, 2016; Rohling et al, 2016). In the present study, after adjusting for CRF, it was observed that total sedentary time was only associated with HbA1c, whereas BST had favorable associations with HOMA-IR, Matsuda index, and fasting glucose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There appears to be a diabetes specific effect on resting HRV, as reductions in resting HRV metrics are apparent in newly diagnosed T1D without a decline in cardiorespiratory fitness (Röhling et al. ). Nevertheless, some of the controversy regarding frequency‐domain HRV analysis warrants consideration.…”
Section: Discussionmentioning
confidence: 99%
“…While these complications are more common in chronic diabetes, the association is not as well described in newly-diagnosed diabetes. In a recent research article published in Diabetes Care [5], investigators recruited 163 recently diagnosed patients with type-1 diabetes mellitus, 188 patients with type-2 diabetes mellitus, and 40 age-matched controls for each group. All study participants underwent HRV assessment and spiroergometry to assess autonomic function and cardiorespiratory fitness during a hyperinsulenemic-euglycemic clamp.…”
Section: Autonomic Dysfunction and Fitness In Patients With Recently mentioning
confidence: 99%